2015
DOI: 10.1002/chem.201502099
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Organocatalytic Approach for the Synthesis of Enantioenriched gem‐Difluorinated Compounds

Abstract: The combination of a practical and highly enantioselective organocatalytic reaction, which allows the stereoselective introduction of a benzodithiol group, with a fluorination step, gives a new and effective strategy for the stereoselective synthesis of difluorinated building blocks. The benzodithiol group is a versatile and chameleonic group that can be further functionalized before fluorination, giving customized and tailored useful synthetic strategies. As an example of the application of this facile strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Following these encouraging results, we evaluated two more electrophiles, namely, tropylium tetrafluoroborate and 1,3-benzodithiolylium tetraborate . For tropylium tetrafluoroborate, we found that once again, the solvent is critical for the reaction outcome, with DMF yielding full conversion of the semibenzene and full selectivity toward the trapped product in less than 30 min, whereas MeCN, acetone, and CH 2 Cl 2 gave very poor selectivity (Table S1).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Following these encouraging results, we evaluated two more electrophiles, namely, tropylium tetrafluoroborate and 1,3-benzodithiolylium tetraborate . For tropylium tetrafluoroborate, we found that once again, the solvent is critical for the reaction outcome, with DMF yielding full conversion of the semibenzene and full selectivity toward the trapped product in less than 30 min, whereas MeCN, acetone, and CH 2 Cl 2 gave very poor selectivity (Table S1).…”
Section: Resultsmentioning
confidence: 88%
“…Following these encouraging results, we evaluated two more electrophiles, namely, tropylium tetrafluoroborate 19 and 1,3-benzodithiolylium tetraborate. 20 For tropylium tetrafluoroborate, we found that once again, the solvent is critical for the reaction outcome, with DMF yielding full conversion of the semibenzene and full selectivity toward the trapped product in less than 30 min, whereas MeCN, acetone, and CH 2 Cl 2 gave very poor selectivity ( Table S1 ). We chose 1,3-benzo dithiolylium tetrafluoroborate as the next electrophile since a similar reactivity to tropylium tetrafluoroborate has been reported for this carbocation, 19d making it a promising candidate to further increase the scope of this newly discovered transformation.…”
Section: Resultsmentioning
confidence: 91%
“…In the presence of tertiary amines, 16 forms carbene, which then dimerizes to tetrathiofulvalene derivatives 101. On the other hand, alkylation without the presence of an inorganic base is also possible, and the procedure was fully optimized 103…”
Section: An Unexpected Journey: Carbenium Ions For Organocatalytic Snmentioning
confidence: 99%
“…In fact, this group can also stabilize negative charges, and by lithiation, the protected intermediates obtained in high enantiomeric excess after the organocatalytic alkylation, could be easily alkylated. Benzodithiol can be also used as a synthetic equivalent of the CO and CF 2 groups,103 as we have recently shown (Scheme ). Using this straightforward methodology, it is possible to install the CF 2 unit near stereogenic centers for the synthesis of complex difluorinated molecules 104…”
Section: An Unexpected Journey: Carbenium Ions For Organocatalytic Snmentioning
confidence: 99%